PERANCANGAN BODI MOTOR MENGGUNAKAN SERAT LONTAR DENGAN METODE VDI 2222 - Jefrianus Bere; Jefri S. Bale; Rima Nindia Selan (Universitas Nusa Cendana, 2023)
The design of several vehicles by changing the design of the vehicle body and household materials using composites has already been carried out in Indonesia using various methods and using natural materials that are easy to find. A unique motorcycle body design can give an attractive impression from the appearance of the motorcycle in use, seen from the new physical conditions with the image of a motorcycle that is easily engineered in such a way that it becomes an opportunity for motorcycle manufacturers to design motorcycle bodies with natural materials that can received potential market share. One of the natural materials that can be made or designed to be used as an alternative to composite raw materials as motor designs that are easy to find in the NTT region is one of them is palm fiber, whose use is still limited.